2020
DOI: 10.1017/s0890060420000098
|View full text |Cite
|
Sign up to set email alerts
|

Humanitarian makerspaces in crisis-affected communities

Abstract: There is an increasing demand for humanitarian aid around the world. At the same time, the number of makerspaces has been growing exponentially. Recently, the humanitarian sector has become interested in how these new design spaces can help crisis-affected populations. Despite the emergence of humanitarian makerspaces, there is little research to date that documents their outcomes and impacts. A multi-case study approach is taken to analyze three makerspaces that support migrants, refugees, and asylum seekers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although this is not the first time that makers and makerspaces have played a role in crisis response (Corsini et al, 2019; Corsini and Moultrie, 2019, 2020), this is the first time that the maker community is responding in such numbers. Prior to COVID‐19, research on 3D printing in the humanitarian sector identified a handful of promising projects (Corsini et al, 2020a).…”
Section: Introductionmentioning
confidence: 95%
“…Although this is not the first time that makers and makerspaces have played a role in crisis response (Corsini et al, 2019; Corsini and Moultrie, 2019, 2020), this is the first time that the maker community is responding in such numbers. Prior to COVID‐19, research on 3D printing in the humanitarian sector identified a handful of promising projects (Corsini et al, 2020a).…”
Section: Introductionmentioning
confidence: 95%
“…Hence, perceived usefulness is a significant determinant which could help learners accept library makerspace and increase its usage. Several researchers have recommended that to retain habitual users and attract new users to the makerspace, motivational factors should be considered (Casakin and Kreitler 2010;Corsini and Moultrie 2020). Motivation has the power to bring people together to exchange ideas and improve their skills.…”
Section: Introductionmentioning
confidence: 99%
“…We know how important the prototype is for the designer's process by supporting him/her in exploring, learning, refining and communicating the product (Camburn et al, 2017), but also for the whole system of actors that contribute to the descent to the market (Preece et al, 2015). There are many definitions of prototype (Jensen et al, 2016) and different taxonomies that help in understanding the relationship of the prototype according to different application contexts, function and goals of use (Petrakis et al, diid 2019), but beyond its phenomenological dimension, it is possible to state with certainty that prototyping significantly increases the performance of the product (Camburn et al, 2017), of the creative process (Corsini & Moultrie, 2017), making it an essential field of experimentation and work for designers.…”
Section: Introductionmentioning
confidence: 99%